PENEGAKAN HUKUM DALAM PENGAWASAN ORANG ASING DI MASA PANDEMI COVID-19 (Jurnal Magister Hukum Perspektif, 2022)
The purpose of this study is to analyze forms of immigration criminal violations committed by foreigners and law enforcement mechanisms in an effort to supervise foreigners during the Covid-19 pandemic. This study uses a normative legal research method, because this research analyzes legal materials based on concepts, theories, laws and regulations, doctrines, legal principles and the author's opinion. The study findings various policy instruments and strategies were issued by General Director of Immigration to overcome the problems due to restrictions on the mobility of people, including foreigners. There are two forms of violation of the Immigration Law, namely administrative violations and pro-justice violations. This study found that the types of violations committed by foreigners include abuse of residence permits, falsification of documents and involvement in human trafficking. The Directorate General of Immigration as the authorized party to enforce immigration law takes action against violators of immigration law who commit administrative and criminal violations in accordance with applicable regulations. There are three recommendations from this study. First, socialization related to immigration services during the pandemic must be increased. Second, it is necessary to build synergy and coordination between Timpora, especially in detecting potential vulnerabilities in the presence and activities of foreigners in Indonesia. Third, a structured law enforcement organizational is needed which clearly and hierarchically on function, controlling, supervised of the law enforcement process. Fourth, improving the competence of immigration personnel needs to be intensified to understand the substance and technicalities, especially in mastering information technology